Bid regulates the pathogenesis of neurotropic reovirus. - Pranav Danthi; Andrea J Pruijssers; Angela K Berger; Geoffrey H Holm; Sandra S Zinkel; Terence S Dermody (PLoS Pathogens)
Reovirus infection leads to apoptosis in both cultured cells and the murine central nervous system (CNS). NF-kappaB-driven transcription of proapoptotic cellular genes is required for the effector phase of the apoptotic response. Although both extrinsic death-receptor signaling pathways and intrinsic pathways involving mitochondrial injury are implicated in reovirus-induced apoptosis, mechanisms by which either of these pathways are activated and their relationship to NF-kappaB signaling following reovirus infection are unknown. The proapoptotic Bcl-2 family member, Bid, is activated by proteolytic cleavage following reovirus infection. To understand how reovirus integrates host signaling circuits to induce apoptosis, we examined proapoptotic signaling following infection of Bid-deficient cells. Although reovirus growth was not affected by the absence of Bid, cells lacking Bid failed to undergo apoptosis. Furthermore, we found that NF-kappaB activation is required for Bid cleavage and subsequent proapoptotic signaling. To examine the functional significance of Bid-dependent apoptosis in reovirus disease, we monitored fatal encephalitis caused by reovirus in the presence and absence of Bid. Survival of Bid-deficient mice was significantly enhanced in comparison to wild-type mice following either peroral or intracranial inoculation of reovirus. Decreased reovirus virulence in Bid-null mice was accompanied by a reduction in viral yield. These findings define a role for NF-kappaB-dependent cleavage of Bid in the cell death program initiated by viral infection and link Bid to viral virulence.